Influence of Microplastics on the Growth and the Intestinal Microbiota Composition of Brine Shrimp - Li, Hongyu; Chen, Hongwei; Wang, Jiao; Li, Jiayao; Liu, Sitong; Tu, Jianbo; Chen, Yanzhen; Zong, Yanping; Zhang, Pingping; Wang, Zhiyun; Liu, Xianhua (Frontiers in Microbiology, 2021)
Microplastics (MPs) are ubiquitous in the aquatic environment and can be frequently ingested by zooplankton, leading to various effects. Brine shrimp (Artemia parthenogenetica) has an important role in the energy flow through trophic levels in different seawater systems. In this work, the influence of polyethylene (PE) and polystyrene (PS) MPs on the growth of brine shrimp and corresponding changes of gut microbiota were investigated. Our results showed that the MPs remarkably reduced the growth rate of brine shrimp, and the two types of MPs have different impacts. The average body length of brine shrimps was reduced by 17.92% and 14.95% in PE group and PS group, respectively. MPs are mainly found in the intestine and their exposure evidently affect the gut microbiota. By using 16S rRNA gene high-throughput sequencing, 32 phyla of bacteria were detected in the intestine, and the microbiome consisted mainly of Proteobacteria, Firmicutes, and Actinobacteria. MPs exposure significantly increased gut microbial diversity. For PE group, the proportion of Actinobacteria and Bacteroidetes increased by 45.26% and 2.73%, respectively. For PS group, it was 54.95% and 1.27% respectively. According to the analysis on genus level, the proportions of Ponticoccus, Seohaeicola, Polycyclovorans, and Methylophaga decreased by 46.38%, 1.24%, 1.07%, and 2.66%, respectively for PE group, and 57.87%, 1.43%, 0.88%, and 2.24%, respectively for PS group. In contrast, the proportions of Stappia, Microbacterium and Dietzia increased by 1.12%, 23.27%, and 11.59% respectively for PE group, and 1.09%, 3.79%, and 42.96% respectively for PS group. These experimental results demonstrated the ingestion of MPs by brine shrimp can alter the composition of the gut microbiota, and leads to a slow growth rate. This study provides preliminary data support for understanding the biotoxicity of MPs to invertebrate zooplankton and is conducive to the further risk assessment of MP exposure.